Model of Islamic Educational Leadership Based on Prophetic Leadership Values: A Literature Review - Iqbal Hakim; Fatimah Zahra (PT. Berkah Smart Academica, 2024)
This literature review examines the concept of Islamic educational leadership, focusing on the integration of Prophetic leadership values. The review synthesizes existing research to explore the historical and contemporary context of Islamic education, the principles of Prophetic leadership, and the potential for developing a leadership model that aligns with Islamic values. Methodologically, the review employs a systematic approach, analyzing relevant scholarly articles, books, and reports. The findings reveal a significant gap in the literature regarding the practical application of Prophetic leadership principles in modern educational settings. The review highlights key themes such as ethical conduct, justice, compassion, and consultation as central to Prophetic leadership. Furthermore, it discusses the challenges and opportunities in implementing such a model, including the influence of Western educational systems and the need for contextualization. The conclusion emphasizes the importance of a leadership model that fosters both academic excellence and spiritual development, ultimately promoting a holistic approach to education that reflects the values of Islam. This review aims to provide a foundation for future research and practice in Islamic educational leadership, offering insights into how educational leaders can embody the qualities of the Prophet Muhammad (peace be upon him) to guide and inspire their communities.